The effectiveness of the mechanisms to manage strikes in essential services in the public health sector, Western Cape, South Africa - Rikwe, Zoliswa (Cape Peninsula University of Technology, 2018)
The principle of the right to strike is internationally documented, as determined by the Committee on Freedom of Association. In South Africa, the right to strike is enshrined and protected in Section 23 of the country's Constitution under its Bill of Rights. Under specific circumstances, the Constitution allows for legislation to limit a right listed in Section 23. At the same time, the Constitution guarantees that everyone has the right to life and health care services. South African industrial action is regulated by the Labour Relations Act (LRA) No. 66 of 1995, as amended, which precludes workers who are employed in essential services from striking, because interruption of these services may endanger lives. However, the LRA also provides for the conclusion of a Minimum Service Agreement (MSA), where minimum services replace essential services. No MSA has been ratified since the LRA was promulgated in 1995. It is on this premise that the author investigated the mechanisms which have been put in place to create a balance between the right to strike and the need to provide essential services in the event of a strike. This study used a qualitative research design. Open-ended questionnaires were distributed to the target research sample. Purposive sampling was applied to a total of 30 participants who were selected from the Western Cape Department of Health's essential services. The qualitative data was analysed using theme identification to make sense of the findings. The research results reveal that employees who are providing essential services have the right to strike only if certain conditions are met. One of these conditions is the conclusion of a Minimum Service Agreement (MSA) to ensure a balance between the rights of health workers to strike and the rights of citizens to be provided with health care services. This agreement provides the duties and responsibilities of the employer and employees for the continuation of minimum services in the event of a public sector strike to ensure that service delivery is not interrupted. Specific recommendations are made by the researcher regarding the MSA, and measures are discussed to ensure that the minimum services within essential services remain operational in the event of a public sector strike.
Thesis (MTech (Human Resource Management))--Cape Peninsula University of Technology, 2018.
Keywords: Strikes and lockouts -- Hospitals -- South Africa -- Western Cape; Labor laws and legislation -- South Africa; Right to strike -- South Africa